Pictorial review: paediatric groin and scrotal lumps and bumps. (November 2013) - Larkman, N; Kingston, K; Murphy, A; Cooper, J
This pictorial review explores the wide spectrum of paediatric groin and scrotal masses. Examples overlap with the adult population but concentrate on those more common in, or unique to, children. Correlation with other imaging modalities is included where appropriate.